MSMEs Empowerment During the Covid-19 Pandemic in the Outer Baduy Tribe Based on Asset Based Community Development (ABCD) - Fitri Yani Jalil; Dinda Rama Haribowo (Universitas Islam Lamongan, 2022)
Abstract The Covid-19 pandemic that has occurred in recent years has had such a huge impact on all elements of society, including the Outer Baduy community in Ciboleger. In addition to the economic impact, changes in consumer attitudes have also changed. This research focuses on the empowerment of MSMEs in the Baduy Luar community in Cibologer by using the Asset Based Community Development (ABCD) method. This study uses a qualitative approach. Data were collected using interview and observation methods. Based on observations, it was found that the Covid-19 pandemic that occurred did not have a significant effect on the MSMEs of the Baduy community. This is due to the existence of traditional values, culture and traditions that have been carried out and have colored the lives of the Baduy people. This valuable asset must always be preserved so that it does not become extinct due to changing times. For this reason, intensive training is needed for entrepreneurs in the Baduy community in order to provide maximum impact. Keywords: MSME Empowerment, Asset Based Community Development method, Covid-19 Pandemic, Baduy community